PEMAHAMAN GURU KIMIA SEKOLAH MENENGAH ATAS TENTANG PENILAIAN KEMAMPUAN BERPIKIR TINGKAT TINGGI DAN IMPLEMENTASINYA - Nurmawati Nurmawati; Elin Driana; Ernawati Ernawati (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2020)
HIGH SCHOOL CHEMISTRY TEACHERS' UNDERSTANDING OF HIGHER-ORDER THINKING SKILLS AND ITS IMPLEMENTATIONAbstractTeachers play an essential role in attempts to develop students' higher-order thinking skills through the implementation of classroom assessments. This study explores chemistry teachers' understanding of higher-order thinking skills (HOTS) assessments, how they implement the assessments, and what obstacles they face. This study employed a qualitative approach that involved 12 high-school chemistry teachers in South Jakarta. Data collection was conducted in August and September 2019 through semi-structured interviews. The findings of this study show that the chemistry teachers have a different understanding of higher-order thinking assessments. The majority of teachers associate HOTS with the three highest levels of the cognitive dimension of Revision of Bloom's taxonomy, critical thinking, and problem-solving. The levels of implementation of HOTS assessments among teachers vary. Among obstacles faced by the teachers are the lack of teachers' knowledge and experience in applying HOTS assessments, variability in students' cognitive abilities, the scarcity of learning facilities, and the lack of guidance and training about HOTS assessments in chemistry. AbstrakGuru memegang peranan penting dalam upaya mengembangkan kemampuan siswa dalam berpikir tingkat tinggi melalui penerapan penilaian kelas.Penelitian ini menggali pemahaman guru kimia tentang penilaian kemampuan berpikir tinggi tinggi (HOTS), penerapannya, dan hambatan-hambatan yang dihadapi. Penelitian ini menggunakan pendekatan kualitatif yang melibatkan 12 orang guru kimia SMA di Jakarta Selatan. Pengumpulan data dilakukan pada bulan Agustus dan September 2019 melalui wawancara semi-terstruktur. Temuan dalam penelitian ini menunjukkan bahwa para guru kimia memiliki pemahaman yang beragam tentang penilaian HOTS. Mayoritas guru mengaitkan penilaian HOTS dengan tiga jenjang tertinggi dimensi kognitif pada taksonomi Bloom yang telah direvisi, berpikir kritis, dan penyelesaian masalah. Tingkat penerapan penilaian HOTS di kalangan guru bervariasi. Hambatan yang dihadapi para guru Kimia SMA dalam melaksanakan penilaian HOTS, antara lain keterbatasan pengetahuan dan pengalaman guru dalam menerapkan penilaian HOTS, kemampuan kognitif siswa yang bervariasi, keterbatasan fasilitas pembelajaran, dan kurangnya panduan dan pelatihan tentang penilaian HOTS untuk mata pelajaran kimia.